Variables asociadas al síndrome de burnout en enfermeras de cuidados intensivos e intermedios del Hospital Regional de Loreto Iquitos 2023 - Aranda Llucema, Norma Lizet (2025)
The objective of this research was to determine the variables that are associated with burnout syndrome in intensive and intermediate care nurses at the Regional Hospital of Loreto Iquitos 2023. The method was quantitative, non-experimental, descriptive, cross-sectional and correlational design. The population and sample were made up of 76 nurses who work in the ICU and Intermediate areas of the Loreto Regional Hospital. The technique was the survey and the instruments were the sociodemographic and work characteristics data sheet and the Maslach Burnout Inventory questionnaire. For data processing, the statistical software IBM SPSS version 24 and Microsoft Excel were used, and for the analysis of the proposed hypotheses, the Chi square statistical test (X2) was used with a significance level of 95% with alpha α = 0.05. The results indicate that 65.8% were between 30 and 45 years old, 93.4% were female, 40.8% had 2 children, 43.4% completed the specialty, 76.4% were in the process of obtaining a master's degree, 53.9% worked in intensive care, 52.6% were appointed, 47.4% had been working at the institution for more than 11 years and 52.6%% had been working in the service for 4 to 10 years. Regarding the Evaluation of Burnout syndrome, 55.3% presented a high level and the remaining 44.7%, a moderate level. In conclusion, a significant association was found between burnout syndrome, age p = 0.001, sex p = 0.010, service where you work p = 0.044, work condition p = 0.018 and time working in the institution p = 0.001.